Buyer Perceptions of Single- and Mixed-Gender Dyadic Sales Teams: Should I have a Wingman or a Wingwoman? - Eric Kushins; Melissa Clark (Journal of Applied Marketing Theory)
Prior research suggests that the gender composition of sales teams may impact team performance. However, research at the intersection of sales, gender, and teams is limited. In this study, we collect survey data from hypothetical buyers who viewed one of six sales pitch videos, including solo salesmen and saleswomen, single-gender dyadic sales teams, and mixed-gender sales teams. The hypothetical buyers were asked to rate each of the salespeople on important traits that have proven to lead to successful sales interactions, including customer orientation, understanding, trustworthiness, awareness of others’ feelings, competence, knowledge, and if the hypothetical buyer would take advice from the salesperson. The findings show buyers evaluate women-only teams higher than men-only teams; salesmen benefit from being a part of a mixed-gender team; and in mixed-gender teams specifically led by a woman, buyer evaluations of customer orientation and other relational and task traits rise dramatically. In dyadic team-based selling, it may be that the most beneficial team structure is a woman lead with a wingman.